2014
DOI: 10.3389/fpsyg.2014.00276
|View full text |Cite
|
Sign up to set email alerts
|

Gender and the performance of music

Abstract: This study evaluates propositions that have appeared in the literature that music phenomena are gendered. Were they present in the musical “message,” gendered qualities might be imparted at any of three stages of the music–communication interchange: the process of composition, its realization into sound by the performer, or imposed by the listener in the process of perception. The research was designed to obtain empirical evidence to enable evaluation of claims of the presence of gendering at these three stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 109 publications
2
13
0
Order By: Relevance
“…It has previously been demonstrated that gendering is not imposed on music by the performer (Sergeant and Himonides, 2014 ); if, as our results demonstrate, gendering is not inherent in musical phenomena themselves, then a necessary conclusion is that gendering originates in the only remaining link in the music communication chain—i.e., by subjective prescription by the listener. In this case, it is possible that the degree of perceived gendering might vary according to the listener's self-concept and degree of sex-self typing.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…It has previously been demonstrated that gendering is not imposed on music by the performer (Sergeant and Himonides, 2014 ); if, as our results demonstrate, gendering is not inherent in musical phenomena themselves, then a necessary conclusion is that gendering originates in the only remaining link in the music communication chain—i.e., by subjective prescription by the listener. In this case, it is possible that the degree of perceived gendering might vary according to the listener's self-concept and degree of sex-self typing.…”
Section: Discussionsupporting
confidence: 64%
“…It has previously been reported that masculine or feminine associations may arise from music when a combination of characteristics of musical valence are present. For example, an impression of masculinity may be gained with faster tempi, but music at slower tempi may be perceived as feminine (Kellaris and Rice, 1993 ; Horn and Costa-Giomi, 2011 ; Sergeant and Himonides, 2014 ). T -tests were therefore applied to data from the Music Characteristics listeners to ensure that no differences were present between female-and male-composed extracts: all tests proved non-significant, confirming that in these respects no such influences could cause bias in data of the composer-sex attribution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…= 1, p = 0.000). As others have shown, gender bias in musical judgments and the tendency to denigrate work linked to or produced by women (Sergeant and Himonides 2014; Schmutz and Faupel 2010) seem even more pronounced among this community.…”
Section: Preferences and Dislikesmentioning
confidence: 69%
“…In modern orchestras, gender proportions are evenly distributed (Sergeant and Himonides 2019), with the percentage of female performers increasing per decade (Dukes et al 2003). Secondly, the structure of the music itself does not contain any characteristics that would allow the performer's gender to be identified (which cannot be inferred from recorded music) (Sergeant and Himonides 2014). The few gender differences documented concern low level perception of music as transient evoked otoacoustic emissions (Cassidy and Ditty 2001), and pitch memory (Gaab et al 2003), which do not take into account the complexity of music.…”
Section: Sexual Selection Theories Of Musicmentioning
confidence: 99%